Todos os caminhos levam à internacionalização? Mapeando o papel da língua inglesa na proposta de especialização do IsF - Mandarino Silva, Nayara Stefanie (Domínios de Lingu@gem, 2024)
The increasingly growing process of internationalization has received different responses. In Brazil, considering the role of languages in the process, the Languages without Borders-Andifes network has proposed a specialization course for internationalization purposes. In this text, I explore the understandings of professors who contributed to the elaboration of this project concerning the role of the English language in this process. I do so by mapping those readings with social cartography. The results indicate tensions and complexities that go from reinforcing to challenging modern/colonial praxis.